2010
DOI: 10.1039/c0cc01506g
|View full text |Cite
|
Sign up to set email alerts
|

The remarkable catalytic activity of the saturated metal organic framework V-MIL-47 in the cyclohexene oxidation

Abstract: The remarkable catalytic activity of the saturated metal organic framework MIL-47 in the epoxidation of cyclohexene is elucidated by means of both experimental results and theoretical calculations.Metal organic frameworks (MOFs) are crystalline porous solids composed of a three-dimensional network of metal ions held in place by multidentate organic molecules. 1,2 Recently, the catalytic applications of MOFs have been reviewed by Hupp et al. and Farrusseng et al. 3,4 However, catalytic reaction mechanisms in m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
85
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 110 publications
(88 citation statements)
references
References 14 publications
3
85
0
Order By: Relevance
“…MOFs usually have high porosity and specific surface areas that make them adequate candidates for catalytic applications both as high-surface-area supports and as intrinsic catalysts. [26,27] MOFs have been used as catalysts for various types of oxidation reactions in the liquid phase, for example, alcohol oxidation, [28] epoxidation, [29][30][31][32] hydrocarbon oxidation, [33][34][35][36] hydroquinone oxidation, [37] the oxidation of organic sulfides, [38] and the oxidation of aromatics. [39] For these oxidation reactions especially, a certain degree of deactivation is frequently observed.…”
Section: Introductionmentioning
confidence: 99%
“…MOFs usually have high porosity and specific surface areas that make them adequate candidates for catalytic applications both as high-surface-area supports and as intrinsic catalysts. [26,27] MOFs have been used as catalysts for various types of oxidation reactions in the liquid phase, for example, alcohol oxidation, [28] epoxidation, [29][30][31][32] hydrocarbon oxidation, [33][34][35][36] hydroquinone oxidation, [37] the oxidation of organic sulfides, [38] and the oxidation of aromatics. [39] For these oxidation reactions especially, a certain degree of deactivation is frequently observed.…”
Section: Introductionmentioning
confidence: 99%
“…This was supported by nitrogen adsorption measurements that showed that the surface area of MIL-47 after a first run dropped from 1225 m 2 /g to approximately 500 m 2 /g, this will surely lead to a decrease of the reaction rate in the additional runs. We have shown previously 30 that even in conditions of severe leaching (TBHP in water), still these leached out species are relatively inert for the epoxidation mechanism as the building of epoxide stops immediately after the hot filtration of the catalysts; whereas the radical formation of the adduct 4 continues. …”
Section: Stability and Regenerability Of The Catalystmentioning
confidence: 99%
“…But in both cases also a significant amount of leached V is observed. Our earlier work 30 showed that after 1 h of catalysis 12.8 % of the V is leached out of the structure with 0.11 mmol of V-sites. In order to reduce this leaching, the catalytic performance of MIL-47 in the oxidation of cyclohexene was analyzed with TBHP/decane as oxidant (see Fig.…”
Section: The Catalytic Performance Of Mil-47 In the Oxidation Of Cyclmentioning
confidence: 99%
See 2 more Smart Citations